AGE RELATED HISTOCHEMICAL STATUS OF BURSA OF FABRICIUS IN JAPANESE QUAIL (Coturnix coturnix japonica) - S.D. Kadam; J.Y. Waghaye (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Histochemical study was conducted on Bursa of Fabricius of 48 normal Japanese quail birds up to four weeks of age, which were divided into four groups of 12 birds each, at the end of first week, second week, third week and fourth week of age, irrespective of sex. In all age groups, moderate to high periodic acid Schiff’s (PAS) activity was observed in the interfollicular connective tissue septa. Weak PAS activity was observed in the cortex in all age group of birds. The surface epithelium showed moderate PAS activity almost in all age group of birds, along with high PAS activity in the apical border of the surface epithelium in group I age of birds which was intense from group II age of birds. High Alcian blue periodic acid Schiff’s (ABPAS) activity was found in the interfollicular connective tissue septa in group I birds which gradually decreased with the advancement of age. High to intense ABPAS activity was observed in the capillaries as well as tunica intima and adventitia of blood vessels in birds of all age groups.